Authority of the Chief of Village in the Customary Mediation of Marriage Disputes: Phenomenon in Madura, Indonesia - Sayful Mujab; Nabila Luthvita Rahma (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2022)
The authority of the Chief of Village, which has so far been limited to mere administrative authority, may apparently be exceeded by the authority of the chief of Village in conducting customary mediation in marriage disputes in Taman Village, Sreseh sub-district, Sampang Regency, East Java, Indonesia, where so far the mediation authority lies in the competence of a certified mediator. In this regard, two questions is discussed in this paper: first, how is process of customary mediation; and the second, how the implications of the customary mediation on family life in the Taman Village of Sreseh district, Sampang, East Java, Indonesia. The research method used is a socio-legal approach by conducting interviews with the Chief of Taman Village, and local academics. Socio-legal selection is limited to methodology and analytically carried out by using the rules of legal research. The results show that the customary mediation process carried out by the Chief of Village is in line with the mediation process carried out by certified mediators with several similarities and one difference. However, the results of customary mediation showed significant successes that surpassed the success rate of court mediation. The implications of the customary mediation process are threefold. First, it brings local values as the basic of customary mediations. Second, it strengthens the local mediation that aids in reducing the divorce rate in Religious Courts. Third, as a breakthrough in the role and function of the Chief of Village as the leader at the village level.